Photogrammetry Technology by Using DJI Phantom 4 RTK in Batang Mahat, Lima Puluh Kota Regency West Sumatera - Junaidi, Junaidi; Syandriaji, Diva (Jurnal Ilmiah Rekayasa Sipil, 2023)
Technological developments in the field of engineering have increased rapidly. The use of geospatial information becomes one of the bases for decision-making related to planning, managing, and evaluating a field, especially in engineering, which includes the field of measurement and making topographic maps or Digital Elevation Model (DEM). High-resolution geospatial information can create a high-resolution Digital Elevation Model (DEM) map that can be very useful in making models or maps of flood-affected areas. This research will use the photogrammetry technology with DJI Phantom 4 RTK to create the DEM data of Batang Mahat located in Lima Puluh Kota Regency, West Sumatra Province. 28 flights at predetermined points had carried out to measure the area of about 9 km2. All the results of photos captured by the drone will be imported to Agisoft Metashape 1.8.2 software to create the DEM data. The DEM was then compared with DEM data from DEMNAS and the measurement data of Batang Mahat by the SDABK office. The result shows that photogrammetry technology using DJI Phantom 4 RTK compared to measurement data and DEMNAS have a similar ground elevation but different river elevation. This is because the photogrammetry by using DJI Phantom 4 RTK is not equipped with LiDAR. An alternative to solve the problem is by combining the DEM data by DJI Phantom 4 RTK with data from terrestrial surveys. However, this method is quite expensive and ineffective in analyzing flood inundation compared to DEM data (8 m resolution) from DEMNAS.